The Development of the American Private Sector in Relation to International Law. From the First Artificial Satellite to The American Space Commerce Free Enterprise Act - Topolska, Paulina (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The active development of technology enbled mankind to realize new programs for the exploration of previously inaccessible areas of the universe hundreds of thousands of kilometers away. The emergence of this new field created the need to ensure its special legal regulation, which would correspond to the specific characteristics of this business. But now we have entered into a phase of re-evaluation of existing legislation of space and we must realise that alongside countries operating in space an has arisen entirely new entity - the private sector. Therefore it is necessary to ask ourselves whether the privatization and commercialization of outer space is legally possible and if it is not pre-cluded by existing treaties. The draft of the latest US Commercial Space Act is undoubt-edly a great advance for key areas of the private sector activity such as remote sensing and new space missions. It provides a sense of confidence for entrepreneurs by strictly regulating issues related to the supervision of private sector entities. However, on the in-ternational scene the question has arisen of whether this act is contrary to international law, especially principles contained in existing space law treaties.